A revised mechanistic model for sodium insertion in hard carbons. Issue 10 (13th August 2020) - Au, Heather; Alptekin, Hande; Jensen, Anders C. S.; Olsson, Emilia; O'Keefe, Christopher A.; Smith, Thomas; Crespo-Ribadeneyra, Maria; Headen, Thomas F.; Grey, Clare P.; Cai, Qiong; Drew, Alan J.; Titirici, Maria-Magdalena
Abstract : Sodium filling inside hard carbon pores demonstrates increasingly metallic character with increasing pore size. Abstract : Hard carbons have shown considerable promise as anodes for emerging sodium-ion battery technologies. Current understanding of sodium-storage behaviour in hard carbons attributes capacity to filling of graphitic interlayers and pores, and adsorption at defects, although there is still considerable debate regarding the voltages at which these mechanisms occur. Here, ex situ 23 Na solid-state NMR and total scattering studies on a systematically tuned series of hard carbons revealed the formation of increasingly metallic sodium clusters in direct correlation to the growing pore size, occurring only in samples which exhibited a low voltage plateau. Combining experimental results with DFT calculations, we propose a revised mechanistic model in which sodium ions store first simultaneously and continuously at defects, within interlayers and on pore surfaces. Once these higher energy binding sites are filled, pore filling occurs during the plateau region, where the densely confined sodium takes on a greater degree of metallicity.